The impact of digitalization on firm performance: examining the role of digital culture and the effect of supply chain capability. Issue 8 (27th September 2022) - Hautala-Kankaanpää, Tuire
Abstract : Purpose: The study examines the impact of digital platforms and supply chain capability on operational performance and tests the mediation effect of supply chain capability. Further, the purpose is to examine the moderating effect of digital culture and sharpen our knowledge of how organizational culture as a contextual factor affects the firm's digitalization. Design/methodology/approach: The data were harvested from 194 Finnish manufacturing companies, and structural equation modeling was used to test the hypotheses. Findings: The findings show that digital platforms positively and significantly affect supply chain capability. Moreover, supply chain capability mediates the relation between digital platforms and operational performance. Further, this study confirms that digital culture is a contextual factor that explains the differences in the effects of digital platforms on firm performance. Originality/value: This study is one of the first attempts to examine the effect of digital culture in the context of digital platforms, supply chain capabilities, and operational performance.